Thickness mode high frequency MEMS piezoelectric micro ultrasound transducers - Dauchy, Florent; Dorey, Robert A. (Springer Science Business Media, 2007)
Thickness mode piezoelectric micro-electromechanical system (MEMS) ultrasound transducers, operating in the 50–75 MHz range, have been fabricated using a composite sol gel technique in combination with wet etching. The composite sol gel technique involves producing a PZT powder/sol composite slurry, which when spun down yields films a few micrometers thick. Repeated layering, and infiltration, has been used to produce PZT films between 20 and 40 μm thick. Due to the low firing temperature (<720°C) it has also been possible to integrate these PZT films with a micro-machined silicon support wafer. These PZT thick films have been structured using a wet etching technique to create free standing pillars that have been shown to resonate in thickness mode in the frequency range of 50–75 MHz. Examples of these structures and their resonant behaviour are pres
Keywords: PZT; Thick Film; Ultrasound; Transducer; pMUT